Association of Headache Syndromes with Hypertension Incidence (Data from SIMPUS Semarang City 2010-2015) - Amalia Augustina Fadlilah; Budiono, Irwan; Ningrum, Dina Nur Anggraini; Alwi, Luqman; Andar, Nadiya Arawinda (Universitas Negeri Semarang, 2024)
Hypertension is one of the serious public health problems facing the world. The prevalence of hypertension in Semarang City increased in 2013 by 27.1% to 37.02% in 2018. This prevalence rate has not reached the target of the Semarang City SDG's related to the hypertension prevalence rate, which is 25%. Hypertension becomes very dangerous when it is not controlled, because if it occurs for a long time, it can cause complications of the disease. One of the most common comorbidities of primary headache disorders is hypertension. The purpose of this study is to analyze the epidemiological pattern of hypertension and headache syndromes, as well as the association of headache syndromes with hypertension incidence by gender and age group. This study is a quantitative research with a nested case control study research design, using data from SIMPUS Semarang City from 2010-2015. The variables in this study were hypertension and headache syndromes. The analysis used was univariate (frequency distribution) and bivariate analysis (chi square test). The results of the study show that hypertension is more experienced in women than men. The most cases of hypertension occur in the age group of 50-59 years (men and women). There was a significant relationship between headache syndromes and the incidence of hypertension in the Puskesmas area throughout Semarang City.